The Reality of Practicing Leadership Skills Among Educational Leaders in Al Madinah Kindergartens - Maha Hassan Elway; Majdaleen Mahmoud Alqaoud (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The study aimed to explore the reality of practicing leadership skills among educational leaders in Madinah kindergartens. The researcher used a descriptive-analytical approach, where the researcher used a modified version of the leadership skills tool that consists of four areas (familiarity with the work system and procedures, the ability to develop methods and methods of work, the ability to negotiate and manage the discussion, and assess accountability). The study sample consisted of 57 educational leaders as an appropriate sample in Medina. The results of the study found that the practice of leadership skills among educational leaders in Medina from their point of view was high by 75.4%, with all areas of leadership metrics being high. It is this" familiarity with the system of work and its procedures " came first with 83.2%. The "accountability estimate" came in second with 76.6%. "Ability to develop methods and methods of work" came in third place with 71.8%. The last one is "ability to negotiate and manage debate" which came in at 67.2%. However, the study found that there were no statistically significant differences between the means of studying sample responses to leadership skills related to educational level, years of experience and number of courses. One of the most prominent recommendations is to enhance the efficiency of educational leaders by providing training opportunities on the practice of leadership and management skills.